Pendampingan Penguatan Kelembagaan Pokdarwis dalam Mengelola Rest Area BUMDes Puncak Saung Naga - Rokhani Rokhani; Winda Amilia; M. Rondhi; Anik Suwandari; Nurul Dwi Novikarumsari (LP3M STAI Darussalam Krempyang Nganjuk, 2022)
The community services was held in Sumber Gading Village, Sumberwringin District, Bondowoso Regency. The period of service activities is carried out from January 26, 2021 to March 11, 2021. This activity aims to: 1) conduct training on newly formed BUMDes; 2) conduct training to strengthen tourism awareness groups (POKDARWIS) in optimizing their functions as village tourism managers who have advantages and local wisdom; and 3) encourage the active role of SMEs and art actors to synergize with BUMDes, POKDARWIS in order to brand tourism. Based on the implementation of activities and discussions during the training, it can be concluded that there is still a need for continued assistance, because the Pokdarwis management and members have just changed personnel. Regarding the selection of business fields to be worked on by Pokdarwis, it still needs assistance, as well as in tourism branding, Pokdarwis still needs assistance whether to brand the Saung Naga peak rest area in branding tourist villages or village tours.